2022
DOI: 10.1001/jamanetworkopen.2022.1245
|View full text |Cite
|
Sign up to set email alerts
|

Physician Perceptions of Palliative Care for Children With Cancer in Latin America

Abstract: This survey study of physicians in Latin America who care for children with cancer investigates their perceptions about and comfort with pediatric palliative care and how their perceptions align with World Health Organization guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
4
24
0
2
Order By: Relevance
“…The Assessing Doctors' Attitudes on Palliative Treatment study evaluated physicians' perceptions about PPC integration within cancer care in Eurasia revealing that a lack of physician education about the purpose of PPC and perceptions of family resistance are significant barriers to integration. [19][20][21] Similar findings have been seen across LMICs, where both medical and lay individuals often perceive PPC as synonymous to end-of-life care. 2,18 In Latin America (LA), specifically, PPC integration within pediatric cancer care remains challenging.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The Assessing Doctors' Attitudes on Palliative Treatment study evaluated physicians' perceptions about PPC integration within cancer care in Eurasia revealing that a lack of physician education about the purpose of PPC and perceptions of family resistance are significant barriers to integration. [19][20][21] Similar findings have been seen across LMICs, where both medical and lay individuals often perceive PPC as synonymous to end-of-life care. 2,18 In Latin America (LA), specifically, PPC integration within pediatric cancer care remains challenging.…”
supporting
confidence: 62%
“…Findings from the Assessing Doctors' Attitudes on Palliative Treatment survey in LA represented the experiences of 874 physicians who care for children with cancer across 17 countries, largely comprising general pediatricians pediatric oncologists, and intensivists; this study demonstrated that most physicians who care for children with cancer had no formal PPC training, and more than a third had no access to PPC experts for consultation. 21 Perceptions of the purpose and role of PPC in LA are variable, ranging from coordination of a pain clinic to comprehensive end-of-life care. 22 Although all countries in LA have national cancer programs and most have laws regulating cancer care, fewer have PPC programs affiliated with cancer hospitals, and access to PPC services is often delayed by deficiencies in personnel and resources.…”
mentioning
confidence: 99%
“…Lien et al [ 16 ] concluded that dying patients can feel care and satisfaction from the patience, care and comfort of nurses. Hospital clinical nurses’ nursing ability and attitude to care for terminally-ill patients directly affect the nursing quality of terminally-ill patients [ 17 ]. However, studies have shown that Chinese nurses have low levels of attitudes and cognitions towards death [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…McNeil and colleagues 4 reported their efforts to understand physician-associated barriers to pediatric palliative care integration in a cross-sectional survey study of physicians in 17 Latin American countries that assessed palliative care perceptions and comfort in providing primary palliative care. 4 Of note, the authors systematically approached adaptation and translation of their previously used Assessing Doctors' Attitudes on Palliative Treatment (ADAPT) survey for physicians in Latin America. Their efforts to translate, iteratively review, back-translate, and pilot the survey before broad dissemination helped enhance the face validity and cultural sensitivity of their instrument.…”
mentioning
confidence: 99%
“…The findings of McNeil and colleagues 4 suggest that implementing primary pediatric palliative care education in Latin America may fill a critical gap and be associated with alleviating child and family suffering in the context of serious illness. As the how, who, and what of global pediatric palliative care education are considered in pediatric palliative care, we can use this opportunity to center equity.…”
mentioning
confidence: 99%